Indicadores de sustentabilidade socioambiental em restaurantes no roteiro Caminhos de Pedra - Bento Gonçalves (Serra Gaúcha/RS) - Finkler, Raquel (My University, 2023)
Gastronomic tourism is an activity that has gained prominence in the recent years, it can provide a unique experience of the cuisine and customs of a location, as well as enable the socioeconomic development of the communities. Innovations in restaurant management can contribute to the expansion of gastronomic tourism, therefore, the adoption of sustainability criteria/actions by enterprises can promote the optimization of their environmental, social and economical performance. Considering these factors, this study aims to propose socio-environmental sustainability indicators for restaurants on a tourist itinerary. To this end, interviews were used as a data collection technique using an interview guide, consisting of 63 questions and managers of seven restaurants located on the Caminhos de Pedra/Bento Gonçalves/RS/Brasil route were interviewed. Research participants indicated the level of importance of sustainability criteria/actions based on the Likert scale (ranging from 1 - least importance - to 5 - greatest importance). Using the results, the coefficient of variation was calculated for each criterion/action. Subsequently, these results were hierarchized and applied to propose socio-environmental performance indicators for restaurants. Some of the sustainability criteria/actions deserve to be highlighted, as they have received a high level of importance from managers, they are: acquisition of food from small producers or of local origin, indication of substitute dishes to meet dietary restrictions, standardization of recipes by through the use of preparation sheets, use of technologies to reduce energy consumption, recovery of frying oil, adoption of effluent treatment systems, waste segregation considering their types, participation in projects focused on valuing local culture, carrying out training for employees with a focus on reducing waste and environmental education for customers aimed at tourist visits to the region. Food waste, according to participants, is concentrated in the post-production stage, and it is important to adopt strategies to reduce it. The adoption of innovations was rated as a relevant action by research participants. Changes in restaurant operations during the pandemic period result from compliance with National Health Surveillance Agency guidelines (Anvisa, 2020). The proposed social and environmental performance indicators were grouped as essential (8 categories and 55 indicators); complementary (8 categories and 30 indicators) and improvement (7 categories and 21 indicators). Socio-environmental sustainability indicators allow the restaurant to determine its level of evolution in terms of sustainability and can be considered a tool for improving the management of a gastronomic establishment. [resumo fornecido pelo autor]
O turismo gastronômico é uma atividade que vem ganhando destaque nos últimos anos, possibilitando uma experiência única da culinária e dos costumes de uma localidade, como também permite o desenvolvimento socioeconômico da comunidade. As inovações na gestão de restaurante podem contribuir para a ampliação do turismo gastronômico, sendo assim, a adoção de critérios/ações de sustentabilidade, por parte dos empreendimentos, promove a otimização do seu desempenho ambiental, social e econômico. O estudo tem por objetivo propor indicadores de sustentabilidade socioambiental para restaurantes de um roteiro turístico. Para tanto, foi utilizada, como técnica de coleta de dados, a entrevista. A partir de um roteiro de entrevista, composto por 63 questões, foram entrevistados gestores de sete restaurantes instalados no Roteiro Caminhos de Pedra/Bento Gonçalves/RS/Brasil. Os participantes da pesquisa indicaram o nível de importância de critérios/ações de sustentabilidade com base na escala Likert (variando de 1 - menor importância - a 5 - maior importância). Por meio dos resultados, foi calculado o coeficiente de variação para cada critério/ação. Posteriormente, esses resultados foram hierarquizados e aplicados à proposição de indicadores de desempenho socioambiental para restaurantes. Alguns dos critérios/ações de sustentabilidade que merecem destaque, por terem obtido elevado nível de importância por parte dos gestores, são: aquisição de alimentos de pequenos produtores ou de origem local, indicação de pratos substitutos para atender a restrições alimentares, padronização de receitas por meio da utilização de fichas de preparo, utilização de tecnologias para redução de consumo de energia, recuperação de óleo de fritura, adoção de sistemas de tratamento de efluentes, segregação de resíduos considerando suas tipologias, participação em projetos com foco na valorização da cultura local, realização de capacitações dos colaboradores com foco na redução de desperdícios e educação ambiental de clientes voltada para visitação turística na região. Os desperdícios, segundo os participantes, concentram-se na etapa de pós-produção, sendo importante a adoção de estratégias para a sua redução. A adoção de inovações foi pontuada como uma ação de relevância pelos participantes da pesquisa. As alterações na operação dos restaurantes no período de pandemia decorrem do atendimento às diretrizes da Agência Nacional de Vigilância Sanitária (Anvisa, 2020). Os indicadores de desempenho socioambientais propostos foram agrupados como essenciais (8 categorias e 55 indicadores); complementares (8 categorias e 30 indicadores) e de aprimoramento (7 categorias e 21 indicadores). Os indicadores de sustentabilidade socioambiental permitem que o restaurante determine seu nível de evolução no que tange à sustentabilidade e podem ser considerados uma ferramenta para o aprimoramento da gestão de um estabelecimento gastronômico. [resumo fornecido pelo autor]
Keywords: Turismo sustentável - Bento Gonçalves (RS); Gastronomia; Turismo; Restaurantes - Bento Gonçalves (RS); Sustainable tourism - Bento Gonçalves (Brazil); Gastronomy; Tourism; Restaurants - Bento Gonçalves (Brazil)